MANGGARAIN CANDIDATE RULER’S JARGON 2015 AND ITS PEDAGOGICAL IMPLICATIONS IN LANGUAGE TEACHING - Darong, Hieronimus C. (Jurnal Pendidikan dan Kebudayaan Missio, 2015)
Abstract: Manggarain Candidate Ruler’s Jargon  2015 And Its Pedagogical  Implications In Language Teaching. This article focuses on the application of systemic Functional Linguistic (SFL) to a language study and an explanation of how this concept as such would be of benefit and fruitful to language teaching by providing a sample of jargon analysis used by the candidate of Manggarain ruler 2015 in terms of field, tenor and mode. Key words: SFL, jargon, register category   Abstrak: Jargon Para Kandidat Bupati Manggarai 2015 dan Implikasi Pedagogisnya Dalam Pembelajaran Bahasa. Artikel ini fokus pada penerapan fungsi sistemik kebahasaan dalam sebuah kajian bahasa dan penjelasannya tentang bagaimana konsep ini bermanfaat dan bermakna dalam pembelajaran bahasa dengan memberikan contoh analysis jargon yang digunakan oleh para kandidat Bupati Manggarai 2015 dalam konteks field, tenor dan mode.                             Kata kunci: SFL, jargon, kategori pendaftaran